Acrossocheilus paradoxus affects benthic resources and communities in a subtropical stream in Taiwan. Issue 6 (29th August 2013) - Wang, Yi‐Kuang
<x xml:space="preserve">Abstract</x> The effects of benthic fish on stream benthic resources and communities have not been effectively studied in subtropical East Asia. This study examined the effects of the Acrossocheilus paradoxus benthic fish on benthic resources and communities in Jiaolong Creek, Central Taiwan. A cage experiment with a no‐fish control and a fish treatment was used to study the effects of A. paradoxus on the mass of algae and detritus and on the density and community structure of algae and macroinvertebrates. Additional diets, nutrient excretion rates, and feeding scars of this fish were also examined. A. paradoxus fed primarily on algae and detritus. The fish treatment had lower chlorophyll a, phaeophytin a, and ash‐free dry mass than the no‐fish control. Areas of concentrated feeding scars by A. paradoxus had consistently lower chlorophyll a than adjacent non‐feeding areas. The mean density of macroinvertebrates was lower in the fish treatment; however, the taxa richness and diversity were higher. Algal and macroinvertebrate communities differed between treatments. A. paradoxus altered the benthic resources and communities in this study.